2022
DOI: 10.3390/bioengineering9040160
|View full text |Cite
|
Sign up to set email alerts
|

Nanopower Integrated Gaussian Mixture Model Classifier for Epileptic Seizure Prediction

Abstract: This paper presents a new analog front-end classification system that serves as a wake-up engine for digital back-ends, targeting embedded devices for epileptic seizure prediction. Predicting epileptic seizures is of major importance for the patient’s quality of life as they can lead to paralyzation or even prove fatal. Existing solutions rely on power hungry embedded digital inference engines that typically consume several µW or even mW. To increase the embedded device’s autonomy, a new approach is presented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…The volume of input dimensions is contingent on the multidimensional Gaussian function circuit. While there exist various circuits that yield PDFs, extant literature confines their application to dimensions of a modest scale, typically less than 16 [20,65].…”
Section: Proposed Design Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…The volume of input dimensions is contingent on the multidimensional Gaussian function circuit. While there exist various circuits that yield PDFs, extant literature confines their application to dimensions of a modest scale, typically less than 16 [20,65].…”
Section: Proposed Design Methodologymentioning
confidence: 99%
“…A broad spectrum of bump circuits has been developed for numerous applications [20]. However, for the purposes of this research, a modified version of the bump circuit (aspect ratio equal to 7) [65], as shown in Figure 3, has been employed to enhance the quality and resilience of the resulting Gaussian curve. Specifically, the adjusted circuit employs a symmetric current correlator (comprising transistors M p1 -M p6 in Figure 3) with a ratio of 2 instead of the non-symmetric version utilized in [41].…”
Section: Gaussian Function Circuitmentioning
confidence: 99%
See 1 more Smart Citation
“…One approach to tackle this challenge involves implementing a cascaded WTA circuit, illustrated in Figure 6. This devised setup integrates three WTA circuits interconnected in a cascaded manner [83]. Figure 7 provides visual representations of the one-dimensional decision boundaries for both the traditional Lazzaro WTA circuit and the proposed cascaded version.…”
Section: Classmentioning
confidence: 99%
“…Given the importance and versatility of GMM, previous studies have investigated GMM computation hardware intensively utilizing dynamic random-access memory (DRAM) 25 , field-programmable gate array (FPGA) 26 – 28 , or analog circuits. However, usually a large number of transistors was required, which inevitably resulted in a high level of complexity 29 . Consequently, without innovative technologies that can dramatically reduce resource demands when dealing with high-dimensional complex distribution functions like GMMs, the advantages of probabilistic inference procedures remain out of reach for numerous applications.…”
Section: Introductionmentioning
confidence: 99%